Working time: concept and some problems of the legal adjusting. (Journal of actual problems of jurisprudence, 2016)
The paper reveals some regulatory issues of working time in the law of the Republic of Kazakhstan. Also discloses the problems of labor law in the Republic of Kazakhstan. Listed new types of regulation of legal relations in the use of working time. Special attention is paid to the definition of working time regulation, marked important statements toregulate the working time.
Keywords: Economic reforms; labour law; time management; result of work; labor legal relations; legal regulations of working time